Internal Marketing: Membangun Merek Perusahaan dengan Employee Branding Bukan Employer Branding - Tri Esti Masita (Universitas Peradaban, 2015)
This article is a literature review that discusses the importance of building brand for the survival of company through internal marketing. Internal marketing is a method of building the image of company through employee branding that encourages employees identifies himself with brand, or a psychological connection between employees and the company's brand where employees internalize the desired brand image and motivated to project the image to the customer and constituent organizations.